The Role of Solvent in Protein Folding and in Aggregation - Vaiana, S.M. (Kluwer Academic Publishers, 2001)
We discuss features of the effect of solvent on protein folding andaggregation, highlighting the physics related to the particulate nature and the peculiar structure of the aqueous solvent, and the biological significance of interactions between solvent and proteins. To this purpose we use a generalized energy landscape of extended dimensionality. A closer look at the properties of solvent induced interactions and forces proves useful for understanding the physical grounds of `ad hoc' interactions and for devising realistic ways of accounting for solvent effects. The solvent has long been known to be a crucially important part of biological systems, and times appear mature for it to be adequately accounted for in the protein folding problem. Use of the extended dimensionality energy landscape helpseliciting the possibility of coupling among conformational changes and aggregation, such as proved by experimental data in the literature.